Brand Preference of Professionals towards Choosing Smartphone in Nepal - Sah, Gunja Kumari (Tribhuvan University Journal, 2021)
It is tough to forecast or assess an individual preference, but it is vital for marketers since it represents an essential step in understanding consumer choice. It is critical to determine brand preference based on the awareness of the customer. The primary objectives of this study are to assess how professional consumers prefer brands in the choice of mobile phones. Business people, private jobholders, government personnel, and farmers are considered professionals for this study. Other goals are to explore the relationship between brand popularity, price, product attributes, social influence, marketing communication, and brand preference and examine the impact of independent variables on brand preference. Data were obtained from the 150 samples of professionals in Kathmandu valley through convenience sampling techniques. A total of 200 questionnaires were circulated, with 179 being collected. From the collected questionnaires, 29 were invalid, while 150 were valid and entered into SPSS 20. The data were analyzed through reliability, validity, descriptive statistics, correlation, and regression analysis. This study proved product attributes and price influenced the Smartphone purchase decision. So, the Samsung Smartphone is the first choice among professionals. It also confirmed the insignificant relationship between social influence and brand preference. Thus, the social context does not aid in purchasing a smart phone. The findings will support smart phone manufacturers in developing strategies based on consumer brand preferences.